Temperature and Humidity Pemantauan System IoT-based Tobacco Oven in South Sakra - Baiq Hanna Kurratul Aini; Lalu Delsi Samsumar; Zaenudin (Journal of Computer Science and Informatics Engineering, 2024)
Tobacco ovens function to reduce the moisture content of wet tobacco leaves through the use of hot air produced by fire. This research uses the Prototype method which includes six stages: Needs Analysis, Rapid Design, Prototype Creation, Initial Use Evaluation, Prototype Improvement, and Implementation. In the initial stage, a needs analysis was conducted for the temperature and humidity monitoring system in tobacco ovens. The second stage involved designing the hardware, software, and system. After that, the Prototype was made in miniature. An initial evaluation is conducted to ensure the system can monitor conditions appropriately and provide accurate sensor data. If errors are found, the Prototype will be corrected in the fifth stage before proceeding to the Implementation stage. The last stage includes testing the system on a miniature oven. This IoT-based system is integrated with the Blynk app, providing real-time oven temperature and humidity monitoring capabilities. Results show that the system works well in monitoring the temperature and humidity on a miniature scale tobacco oven. Keywords: Tobacco Oven, IoT, Temperature Pemantauan, Humidity, Prototype, Blynk.